Purifying agents for produced fluid from chemical flooding in conventional and heavy oil reservoirs. (February 2019) - Liu, G L; Zhang, F S; Sun, J H; Li, X N; Qu, Y Z; Zhu, Z Y; Su, H M
Abstract: Compared with water flooding, the produced wastewater quality of polymer flooding and ASP flooding has changed significantly. The effect of chemical flooding agent on the stability and purification process of oil droplets and suspended solids in wastewater was analyzed. The two-stage sedimentation-pressure filtration process and the continuous batch sedimentation-two-stage filtration process used in the treatment of chemical flooding wastewater are introduced. The application of organic flocculants, inorganic flocculants, reverse demulsifiers, chemical desiliconizing agents and other purifying agents in the treatment of chemical flooding wastewater is summarized. The key research directions of wastewater treatment from chemical flooding in the future are put forward.